Analisis Usability Pada Sistem Informasi FILKOM Apps Fakultas Ilmu Komputer Universitas Brawijaya - Moch. Baharrudin; Niken Hendrakusma Wardani; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Faculty of Computer Science Brawijaya University create a web-based application to facilitate the work of stakeholders. Application was named Filkom Apps. the observations found that does not display any information. Empty menu will affect user expectations of the system. User do not know the existence of logbook guidance, while logbook feature is one of the main features. Therefore it necessary to evaluate usability, to measure application usability level based on 5 usability aspect efficiency, effectiveness, learnability, memorability and satisfaction. Methods of usability testing, observation and interview are used to measure usability level and to explore problem that related to usability by given task scenario to users. The result of usability testing shows that the value of efficiency (86%), effectiveness(87,5%), learnability has gap 1,35 between test 1 and test 2. Memorability improves the ability of the number click and the number of steps. Satisfaction measured by a SUS questionnaire get scored 65 under the average standard (68). There are some problem related content, navigation and layout. Usability problem found during testing was given improvement recommendation to increase the usability level.